Familiar Others Emiria Sunassa, Eduardo Masferre and Yeh Chi Wei, 1940s-1970s - Scott, Phoebe (National Gallery Singapore, 2022)
Who is "the Other"? What does it mean to represent peoples who are different from one's own? For the modern painter and photographer, images of "Others" were often important sources of inspiration. Artworks might emphasise differences between people-by drawing upon exotic stereotypes about so-called "primitive" cultures-but could also be used to assert a position of solidarity with marginalised communities. The exhibition Familiar Others explores this through the work of the work of three artists. Painter Emiria Sunassa (1894‒1964) made images of peoples from all over the Indonesia archipelago but had a special interest in Papua. Eduardo Masferré (1909‒1995) photographed peoples of the Cordillera region, where he spent his life. Yeh Chi Wei (1913‒1991) travelled throughout Southeast Asia, but was especially inspired by the Indigenous Peoples of Sarawak and Sabah. This catalogue features an essay by curator Phoebe Scott, full-colour images of the artworks, timelines of the three artists, and the artwork responese by artists, poets, academics and musicians that were commissioned for this exhibition.